Effects of crude protein and non-essential amino acids on growth performance, blood profile, and intestinal health of weaned piglets - Correia, Amanda Medeiros; Genova, Jansller Luiz; Saraiva, Alysson; Rocha, Gabriel Cipriano (Frontiers in Veterinary Science, 2023)
This study investigated the effect of crude protein (CP) and non-essential amino acids (NEAA) supplementation on the growth performance, blood profile, intestinal morphology, mRNA relative abundance of inflammatory and antioxidant markers, and tight junction proteins in piglets over the first two weeks after weaning. Ninety 21-day-old piglets (7.55 ± 0.72 kg) were assigned in a randomized block design to one of three dietary treatments: high-CP, diet with 24% CP, low-CP, diet with 18% CP, and low-CP + NEAA, diet with 18% CP supplemented with 5 g/kg Arg (L-arginine), and 10 g/kg Glu+Gln (m L-glutamine and L-glutamate). There was an improvement (P < 0.05) on feed conversion ratio of piglets fed high-CP diet compared to low-CP or low-CP + NEAA. Serum urea nitrogen was higher (P < 0.05) in piglets fed high-CP compared to other dietary treatments. In the duodenum, the villus height of animals fed low-CP + NEAA diets was greater (P < 0.05) than those fed high-CP and low-CP. The goblet cells proportion of piglets fed low-CP + NEAA or high-CP was higher (P < 0.05) compared to low-CP. In the jejunum, the crypt depth of the piglets with high-CP was greater (P < 0.05) in comparison with low-CP + NEAA. In the jejunum, IFN-γ mRNA expression was higher (P < 0.05) in animals fed high-CP compared to other treatments. However, superoxide dismutase and occludin mRNA expression were higher (P < 0.05) in animals fed low-CP+NEAA than in piglets fed high-CP. In the ileum, the number of Peyer’s patches in piglets fed high-CP was higher (P < 0.05) compared to other dietary treatments. In conclusion, high-CP diet (24% CP) improves the feed conversion of piglets in the first two weeks after weaning compared to the low-CP (18% CP) supplemented or not with NEAA. However, the low-CP supplemented with NEAA improves intestinal health in piglets by promoting greater villus height and proportion of goblet cells in the duodenum, reducing jejunal crypt depth and Peyer's number patches in the ileum. In addition, low-CP + NEAA diet showed an increase in superoxide dismutase and occludin, and a lower expression of IFN-γ mRNA.